Elastic stable intramedullary nail combined with Kirschner wire (E-K) technique for treating pediatric distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures - Liu, Yunlong; Ding, Sheng; Yang, Yancai (Frontiers in Pediatrics, 2024)
Objective Elastic stable intramedullary nail (ESIN) is a commonly used method for treating diaphyseal fractures of the tibia, but its application in Distal Tibial Diaphyseal Metaphyseal Junction (DTDMJ) fractures has been a subject of controversy. This study aims to evaluate the clinical efficacy of the Elastic stable intramedullary nail-Kirschner wire (E-K) technique in treating pediatric DTDMJ fractures, providing better clinical decision-making for clinicians in diagnosing and treating such fractures. Methods We conducted a retrospective analysis of patients aged 3–9 years who received treatment at our hospital from January 2019–January 2021 for distal tibial diaphyseal metaphyseal junction (DTDMJ) fractures. Based on their surgical procedures, they were categorized into the Elastic Stable Intramedullary Nail—Kirschner wire group (E-K) and the ESIN group. Demographic data, surgical duration, clinical outcomes, complications, and imaging data were recorded. Results The study included a total of 57 patients, with 24 cases in the E-K group and 33 cases in the ESIN group. There were 30 males and 27 females. The average age was (6.25 ± 1.59) years in the E-K group and (6.27 ± 1.48) years in the ESIN group. There were no significant differences between the two groups in terms of gender, age, weight, time from injury to surgery, follow-up time, side of injury, associated injuries, nail site infection, deep infection, and nail removal time (P > 0.05). Neither group experienced nonunion or refracture. The E-K group exhibited significantly lower coronal and sagittal plane angular values at the final follow-up compared to the ESIN group (P < 0.001). In the E-K group, the final follow-up coronal plane angle was 2.67 (1.09)°, while in the ESIN group, it was 6.55 (2.05)°. The final follow-up sagittal plane angle was 3.12 (1.54)° in the E-K group and 7.58 (1.48)° in the ESIN group. Both groups showed good alignment in the initial postoperative x-rays, with no statistically significant differences. However, during clinical healing, the ESIN group exhibited significant displacement, whereas the E-K group had minimal displacement, demonstrating a significant statistical difference (P < 0.001). There was a statistically significant difference in the AOFAS joint function assessment between the two groups (P = 0.027). Conclusion The E-K technique is a viable option for treating DTDMJ fractures in pediatric patients, with well-established clinical efficacy. Its advantages include a straightforward surgical procedure, safety, and a low incidence of severe complications.